Exploring the Influence of Colors on Primary School Learning Environments: A Psychophysiological Perspective - Zufra Ashraf; Deepti Pande Rana (Recent Trends in Social Studies, 2024)
Primary schools are thought of as a child's first educational experiences and should be planned with a supportive learning environment that supports the desired learning goals. This study's primary goal is to investigate how colors, a significant visual component of design, affect a child's psychophysiological and behavioural characteristics. The impact of prolonged exposure to a monochrome classroom on primary education is examined in this study. Depending on how color is used, it can have different effects on elementary school learning environments. Depending on the color, either one (monochromatic) or a combination of colors may have a varied effect on the student. The research paper involves investigating the effects of warm and cool colors in a classroom and the impact on child development and learning.It makes a particular effort to pinpoint colors that enhance abilities and behaviour while appreciating the differences in influence between the two extremes of warm and cool hues. The study involves various emotional and psychological impact of different colors on primary school students. This study utilizes a mixed-methods approach, integrating quantitative data analysis with qualitative observations and surveys to thoroughly examine the varied impacts of color within primary school settings. Through analyzing physiological responses such as heart rate variability and electrodermal activity alongside behavioral cues like attention span and task performance, the goal is to gain a comprehensive insight into how color influences the learning process. Moreover, it explores the potential influence of cultural and individual disparities in color perception and preference, acknowledging the diverse backgrounds and sensitivities of primary school students. Ultimately, the research findings aim to inform the development of evidence-based design principles for crafting stimulating and conducive learning environments in primary schools.
Keywords: Primary education; classroom color; color preference; primary school; skill development